A critical analysis of the factors influencing peaceful coexistence between Rohingya refugees and host communities in Cox’s Bazar, Bangladesh - Khan, Abdul Kadir (Frontiers in Human Dynamics, 2024)
IntroductionBangladesh currently hosts over a million Rohingya refugees in 33 fetid, dire, and confined camps, with the majority arriving after the 2017 military crackdown in Myanmar’s Rakhine state. Although Rohingya refugees have been arriving in Bangladesh since the 1970s, the mass influx following the 2017 military hostilities in Myanmar’s Rakhine State marked a significant crisis escalation. Initially, the local host communities displayed positive, sympathetic attitudes toward the refugees. However, recent evidence suggests a significant decline in social cohesion and peaceful coexistence, with host communities expressing diminished sympathy and growing concerns over the refugees’ prolonged presence in Cox’s Bazar.ObjectivesThis paper investigates the factors influencing the peaceful coexistence between Rohingya refugees and host communities, drawing on the perspectives of development and humanitarian service providers in the Ukhiya and Teknaf sub-districts of Cox’s Bazar.MethodsThe study utilized a mix of theoretical literature and empirical data to identify five determining factors: economic, social, political, cultural, and environmental. Data collection included 18 in-depth key informant interviews, supplemented by analyses of secondary sources drawn from both gray and academic literature.FindingsThe findings indicate that perceived outgroup threats are increasingly undermining peaceful coexistence, despite the absence of direct conflicts between the host and refugees. While political and cultural factors have remained relatively stable, social, economic, and environmental factors continue to erode the current status of peace.DiscussionThe study highlights spatial and psychological proximity as critical overarching factors in fostering peaceful coexistence. It concludes that closer proximity heightens integrated threats, whereas maintaining optimal distance enhances the likelihood of peaceful coexistence. Therefore, the Rohingya response plan should incorporate conflict-sensitive strategies to tackle the adversity of threat factors while maintaining social cohesion as promoting peaceful coexistence between hosts and refugees.